Prognostic significance of histologic classification and tumor disappearance rate by computed tomography in lung cancer - Kim, Dohun; Kim, Hong Kwan; Kim, Seok-Hyung; Lee, Ho Yun; Cho, Jong Ho; Choi, Yong Soo; Kim, Kwhanmien; Kim, Jhingook; Zo, Jae Ill; Shim, Young Mog (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2018)
Background: We investigated the prognostic value of the International Association for the Study of Lung Cancer (IASLC)/American Thoracic Society (ATS)/European Respiratory Society (ERS) classification and assessed the relationship between pathologic invasiveness and tumor disappearance rate (TDR) in lung adenocarcinoma with ground-glass opacity (GGO). Methods: We reviewed data from 202 consecutive patients operated on between 2000 and 2009 for clinical T1-2N0 lung adenocarcinoma with GGO and reclassified their histologic subtypes according to the IASLC/ATS/ERS classification. Thirty-nine patients had adenocarcinoma in situ (AIS), 29 minimally invasive adenocarcinoma (MIA), 75 lepidic predominant invasive adenocarcinoma (LPA), and 59 non-lepidic predominant invasive adenocarcinoma (NLPA). Survival outcomes were compared according to histologic subtype and TDR. Results: The mean age was 58 years and 101 patients (50%) were male. Lobectomy was performed in 161 patients (79.7%), wedge resection in 34 (16.8%), and segmentectomy in 7 (3.5%). Patients with AIS, MIA, and LPA had significantly smaller tumor sizes, earlier pathologic T stages, and lower incidences of lymphatic/pleural invasion than those with NLPA. The 5-year recurrence-free survival (RFS) rates were 95.1%, 94.5%, and 87.6% in the AIS + MIA, LPA, and NLPA groups, respectively (P=0.029). Tumors with a TDR>75% were associated with lepidic predominant histologic subtype and less pathologic invasiveness. The 5-year RFS rates were 97.4% in tumors with a TDR >75% and 87.8% in tumors with a TDR ≤75% (P=0.0009). Conclusions: Histologic subtype according to the IASLC/ATS/ERS classification and TDR both correlated with pathologic invasiveness and predicted survival in patients with lung adenocarcinoma with GGO.